Effects of EC Plastisizer and SiO2 Nano-Filler on Electrical and Thermal Properties of Chitosan-G-PMMA based Solid Polymer Electrolytes - Kartini. Jaafar, Nor; Malik Marwan Ali, Ab; Zu Azhan Yahya, Muhamad; Zakaria, Rosnah; Zafirah Zainal Abidin, Siti (International Journal of Engineering and Technology, 2019)
Composite grafted polymer electrolyte based on chitosan grafted poly(methyl methacrylate) (Ch-g-PMMA) have been prepared and investigated. The lithium triflouromethanesulfate salt (LiCF3SO3 or LiTf), ethylene carbonate (EC) and SiO2 are applied as a salt, plasticizer and ceramic filler, to the polymer host system. Impedance spectroscopy was performed at room temperature. The highest conductivity of 1.63 x 10-4 Scm-1 was obtained for the grafted polymer with 50 wt. % of LiCF3SO3 and enhanced to 2.23 x 10-4 Scm-1 with the addition of 30 wt. % EC. The conductivity is further enhanced to 4.21 x 10-4 Scmâˆ’1 with the addition of 6 wt. % SiO2. Both additives caused a reduction of the Ch-g-PMMA crystalline phase content and increased segmental flexibility leading to conductivity enhancement.Â Â